Working Remains - Emmett, Rory (Michaelis School of Fine Art, 2024)
Working Remains grapples with colonial legacies and their remnants inscribed on the cultural, socio-political, and topographical contemporary Cape landscape. The remnants suggested by the project's title pertain to concerns about self, place, labour, and culture that permeate personal, and collective history and memory. Working Remains adopts a self-reflexive and critical approach to representation through painting, installation, sculpture, performance, and video.